Preserving land within Riley County and Manhattan, Kansas: conservationist and developer approaches to land planning - Farley, Joshua C. (Kansas State University, 2013)
Increasing population in Manhattan, Kansas and rising enrollment at Kansas State University have increased the interest in establishing new residences and commercial businesses within the city limits. Locations for development include the revitalization of Manhattan’s south end and sites adjacent to Seth Child Road, US Highway 24, and K-177. Recent development patterns in Manhattan, such as residential development near Wildcat Creek, have resulted in severe environmental impacts. While most development enhances existing land use patterns, undeveloped natural areas along K-177 present several environmental opportunities and restraints that must be assessed and well-planned for to accommodate projected growth in a sustainable way. Topography, existing vegetation, drainage networks, wildlife habitats, and proximity to the Kansas River contribute to limitations in development along and extending from K-177. This proximity and resulting development could reduce existing wildlife habitat, plant species, and the overall health of Manhattan’s and the surrounding area’s air, soil and water quality. Developmental strategies are needed to ensure the conservation of sensitive ecosystems and to direct development to the most suitable areas. After conducting an inventory of the land’s natural resources and land use patterns, two suitability models were created to express areas most suitable for development based on two sets of values; conservation-minded and developer-minded. As sites for development were located and assessed, a trail suitability model was then created to express potential connections between new and old development and to show links to other significant destinations. This trail system also establishes greenway selection criteria, aiming to further protect remaining natural areas while providing a public amenity. Fulfillment of the goals and objectives of the Gateway to Manhattan Plan (GMP), establishes development suitability through a conservationist approach to ensure significant preservation of land. Such an approach and related conservation strategies are then discussed to act as a platform for decision making as lands along K-177 are developed. The trail suitability study and proposed greenway network provide solutions for meeting the GMP’s goals of establishing multi-modal connectivity along and across K-177 while conserving environmental resources. In addition to controlling development patterns, these greenways will act as conduits for wildlife, help maintain or enhance air, soil and water quality, protect endangered flora and fauna, and provide recreational amenities while minimizing overall negative environmental impacts.
Keywords: Land Conservation; Conservation Development; Greenways; Land Use Planning; Suitability Analysis; Environmental management (0474); Landscape Architecture (0390); Land Use Planning (0536)